Undergound aka Podzemlje aka Bila jednom jedna zemlja . Underground – aka Once Upon a Time There Was a Country - Kusturica, Emir (Ciby 2000 Paris ; Baumgartner, Karl ; Spengler, Pierre ; Ćatović, Maksa, 1995)
Based on Dušan Kovačević’s story, the film focuses on two crooked communist activists –manipulative charmer Marko and his best friend, foolishly impulsive Crni. After the German invasion of Yugoslavia, the two friends jointly undertake some acts of resistance as well as some profitable business. They also share a passion for Natalija, an actress under the protection of a Nazi officer whom Crni quickly kills. In order to keep Natalija only for himself, Marko arranges a cunning scheme. Under pretence of protection, he keeps Crni and other memebers of the resistance locked into the basement of his house where they produce weapons. After the war is over, Marko, now a war hero and Tito’s associate, continues to give them fictitious reports of German victories in order to go on making a profit from the arms production. During an underground wedding, Crni and his son find their way up and although it is 1961, their belief in Nazi rule is reaffirmed as they find themselves on the set of a movie about the German occupation. In an allegorical if dubious final part, all of the main characters find themselves in Slavonia during the 1991 war in Yugoslavia.